2009
DOI: 10.1542/peds.2008-3037
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Parenting Styles and Teen Driving, Safety-Related Behaviors and Attitudes

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Authoritative parenting style is known to influence adolescent behaviors and attitudes positively. However, little is known about the interplay between parental warmth, support, and control in relation to teen driving safety. WHAT THIS STUDY ADDS:Parents matter. This study confirms that safe driving belongs on the list of adolescent behaviors known to be influenced positively by authoritative parenting. abstract + OBJECTIVE:The goal was to explore the association between parenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 75 publications
(95 reference statements)
1
34
0
6
Order By: Relevance
“…A cross-sectional study with a nationally representative sample of 9th-, 10th-, and 11th-grade students found that teenagers with authoritative parents who exhibited both warmth/support and monitoring were 71% less likely to drive while impaired compared with those who had uninvolved parents (Ginsburg et al, 2009). However, the analyses did not control for the teenager's substance use.…”
Section: Factors Associated With Teenage Dwi and Rwimentioning
confidence: 99%
“…A cross-sectional study with a nationally representative sample of 9th-, 10th-, and 11th-grade students found that teenagers with authoritative parents who exhibited both warmth/support and monitoring were 71% less likely to drive while impaired compared with those who had uninvolved parents (Ginsburg et al, 2009). However, the analyses did not control for the teenager's substance use.…”
Section: Factors Associated With Teenage Dwi and Rwimentioning
confidence: 99%
“…In cross-sectional studies of DWI risk, male gender, 11 previous driving offenses, 12 risky driving, 10 riding with an impaired driver (RWI), 11 poor family relationships, 13 and lack of parental monitoring 14 were found to be associated with teenage DWI. The most consistent predictor of DWI in studies in adolescent samples is problem drinking, including heavy alcohol use and drinking-related problems.…”
mentioning
confidence: 99%
“…El énfasis de la investigación en esta área, con población adolescente, ha estado puesto en estudiar el rol parental en la conducción durante la etapa de novicio [11][12][13][14] . Los resultados muestran que las prácticas parentales juegan un rol fundamental en el involucramiento de conductas de riesgo en la conducción de estos jóvenes 11,14 .…”
unclassified
“…Los resultados muestran que las prácticas parentales juegan un rol fundamental en el involucramiento de conductas de riesgo en la conducción de estos jóvenes 11,14 . Los investigadores han encontrado que adolescentes cuyos padres ponen más reglas respecto de la conducción, supervisan la conducta del adolescente y los apoyan, se involucran menos en violaciones de normas del tránsito y en accidentes 14 . Por esa razón, proponemos que las prácticas parentales también influirán en las conductas de los adolescentes como peatones.…”
unclassified